Penerapan Metode Guided Writing untuk Meningkatkan Keterampilan Menulis Tegak Bersambung Siswa Kelas II SD - Resky Damayanti Mustari; Rosdiah Salam; Andi Makkasau (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
This research was motivated by the low cursive writing skills of class II students at SDN 81 Pinrang, Pinrang Regency. This study aims to describe the application of the guided writing method in improving the cursive writing skills of class II students at SDN 81 Pinrang. This type of research is PTK. The research subjects were teachers and grade II students at SDN 81 Pinrang with a total of 24 students consisting of 11 boys and 13 girls. Data collection techniques used are observation, tests and documentation. The data analysis technique used is a qualitative approach. The results showed that the teacher's teaching activities and student learning activities in the first cycle were in the sufficient category and in the second cycle they were in the good category. The results of students' cursive writing skills in cycle I were categorized as incomplete and in cycle II students' cursive writing skills were categorized as complete. The conclusion of this study is that the application of the guided writing method can improve the cursive writing skills of class II students at SDN 81 Pinrang.